Organismo de gestión de destinos (OGD) para la comercialización de productos y servicios turísticos sostenibles en la provincia de Manabí - Bermeo Macías, Silvia Elizabeth (2021)
The main objective of this research was to structure a destination management body (DMO) that contributes to the commercialization of sustainable tourism products and services in Manabí province. Which is presented in three phases: analysis of the tourist territory in Manabí, evaluation of comparative and competitive advantages and approach of the OGD. It was determined through the bibliographic and documentary review supported by the cadastre and inventory files that Manabí is a destination that has general conditions for the development of the activity, with a sufficient but not optimal offer, which through the interview and the matrix of involved made it possible to identify the key actors and their needs. It was established with a matrix of potentialities that 6 provincial attractions have greater tourist potential, as well as through interviews the competitive advantages that are the proximity of their cantons, the gastronomy and their beaches were established, while the disadvantages are the deficient infrastructure, the lack of coordination governance and marketing; which were evaluated from the competition matrix against three destinations. Finally, the management organization for Manabí was proposed with its structure outlining functions and responsibilities under a model that focuses on sustainable development through processes such as strategic planning and research, equipment and services, marketing and promotion, as well as governance and interinstitutional strengthening that, in turn, are constituted as strategic axes, from which 14 projects are broken down with their respective management indicators.